Comparison of two successive versions 6 and 7 of TMPA satellite precipitation products with rain gauge data over Swat Watershed, Hindukush Mountains, Pakistan. (16th March 2016) - Anjum, Muhammad Naveed; Ding, Yongjian; Shangguan, Donghui; Tahir, Adnan Ahmad; Iqbal, Mudassar; Adnan, Muhammad
Abstract: Swat watershed in Hindukush Mountains was selected for the evaluation of Tropical Rainfall Measuring Mission (TRMM) Multi‐satellite Precipitation Analysis (TMPA) Versions 6 and 7 using rain‐gauge data. Agreement between the satellite and gauge estimates was good at monthly scale but poor at daily and seasonal (monsoon and westerlies, particularly for monsoon) scales. Over and underestimations were observed at foothills and high‐altitude areas, respectively. Although, bias was still present, but overall performance of TMPA‐V7 was improved compared with TMPA‐V6. Bias corrected‐TMPA‐V7 estimates were better than corrected‐TMPA‐V6. Basin average bias‐corrected precipitation estimates of TMPA‐V7 were estimated at daily, monthly, westerlies, monsoon, and annual scales [means (mm) 1.60, 48, 190, 173 and 582, respectively] for the period 1998–2014. Results suggest that regional bias correction of satellite‐precipitation products is critical and can yield to the substantial improvement in capturing the precipitation.